(untitled) (GEOgraphia, 2021)
Os empreendimentos industriais chamados de “grandes projetos” são uma designação comum nas pesquisas acadêmicas e nos estudos produzidos pelas autarquias de planejamento econômico do Espírito Santo. Abordados como parte de um “novo ciclo de desenvolvimento” estadual mediante a “atuação decisiva” do Estado entre os anos 1970 e 1980, os “grandes projetos”, em seus nexos com a modernização do Espírito Santo, deveriam ser reinterpretados. Nosso objetivo principal foi abordar os fundamentos dessa modernização na sua relação com a particularidade capixaba, a partir da ampliação do setor de papel e celulose e da construção da Aracruz Celulose. Palavras-chave: “grandes projetos”; Aracruz Celulose; modernização; crise; capital fictício. THE MODERNIZATION OF ESPIRITO SANTO IN THE 1970’S AND 1980’S AND THE FUNDAMENTAL CRISIS OF CAPITAL: AN APPROACH STARTING FROM SECTOR OF PAPER AND CELLULOSE WITHIN THE SCOPE OF “LARGE-SCALE PROJECTS” Abstract: The industrial enterprises called “large-scale projects” are a common designation in academic research and in studies produced by autarchies of economic planning of Espirito Santo. Approached as part of a “new term of development” of Espírito Santo through decisive action of State between the 1970’s and 1980’s, we defend that “large-scale projects” concerns what we understand have been the integration of Brazil and Espirito Santo into process of catch-up modernization (KURZ, [1991] 1996). Therefore, our objective was approached the foundations of this modernization and how it achieved the periphery of the world and the Brazilian and Espírito-santense spatialities. To proceed to this understanding, we focus the focus on the sector of paper and cellulose and the building of Aracruz Cellulose factory, an of main enterprise of “large-scale projects”. Keywords: “large-scale projects”; Aracruz Cellulose factory; modernization; crisis; fictitious capital. LA MODERNIZACIÓN DE ESPÍRITO SANTO EN LOS AÑOS 1970 Y 1980 Y LA CRISIS FUNDAMENTAL DEL CAPITAL: UN EXAMEN DESDE EL SECTOR DEL PAPEL Y DE LA CELULOSA EN EL ÁMBITO DE LOS “GRANDES PROYECTOS” Resumen: Las empresas industriales llamadas “grandes proyectos” son una denominación común en la investigación académica y en los estudios emprendidos por las autarquías de planificación económica en el estado de Espírito Santo (Brasil). Abordado como parte de un “nuevo ciclo de desarrollo” estatal a través de la acción decisiva del Estado, entre las décadas de 1970 y 1980, sostenemos que los "grandes proyectos" se refieren a lo que entendemos ha sido la integración de Brasil y Espirito Santo al proceso de modernización retrasada (KURZ, [1991] 1996). Así, nuestro objetivo es abordar los fundamentos de esta modernización y como ella llegó a la periferia del mundo en general y las espacialidades brasileñas y de Espírito Santo en particular. Para lograr este análisis nos enfocamos el sector de papel y celulosa y de la construcción de Aracruz Celulose, uno de los principales emprendimientos de los denominados “grandes proyectos”. Palabras clave: “grandes proyectos”; Aracruz Celulosa; modernización; crisis; capital ficticio.